Analisis Hubungan antara Beban Kerja Mental dan Stres Kerja pada Perawat di Rumah Sakit X - Maria Saraswati Kinasih Hapsari; Raden Bonifacius Bayu Erlangga Kusuma; Anggit Wirama Siwidati (Universitas Airlangga, 2025)
Background: A mismatch between job requirements and individual abilities can lead to reduced performance due to work-related stress. Work stress affects many professions, but nurses at Hospital X experience it most frequently. A national Indonesian survey reported that 50.9% of nurses across the country experienced work stress in 2018. Previous studies have also examined how stress levels among nurses are associated with individual characteristics (such as age, gender, and length of service) and the mental workload they face. Objectives: This study examined which nurse characteristics, combined with their mental workload, influence their work-related stress levels. Methods: This study used a cross-sectional quantitative design to collect data from nurses at Hospital X in August 2025 through the distribution of the NASA-TLX and ENSS questionnaires. A total of 30 nurses participated through purposive sampling. Frequency distribution tables were used for univariate analysis, while chi-square and Fisher’s exact tests were performed for bivariate analysis. Results: The univariate analysis showed that 63.3% of participants were under 29 years old, 90.0% were female, and 53.3% had worked for less than four years. The results also indicated that 56.7% of participants experienced a high mental workload, while 60.0% reported low levels of work stress. Bivariate analysis using the chi-square test revealed a significant relationship between mental workload and work stress (p=0.035). However, no significant relationships were found between age and work stress (p=0.266), gender and work stress (p=0.548), or length of service and work stress (p=0.765). Conclusion: This study found that mental workload significantly affects work stress levels among nurses at Hospital X. However, age, gender, and length of service were not found to influence work stress among nurses in this setting.